2007
DOI: 10.1103/physrevlett.99.110602
|View full text |Cite
|
Sign up to set email alerts
|

Crossover from Superdiffusive to Diffusive Mixing in Plastically Deformed Solids

Abstract: We derive expressions for the effective diffusion coefficient of Richardson's pairs in plastically strained solids as a function of the pair separation distance R. We predict that a crossover from superdiffusive to diffusive mixing takes place when R becomes comparable to the coherence length of the shearing events underlying the plastic deformation. Molecular dynamics simulations on nanocrystalline and amorphous systems support this analysis, which thus provides new insight on deformation mechanisms in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The understanding of the mechanism could help to explain and classify various athermal atomic transport processes known in the literature such as superdiffusion on solid surfaces 5,14,15,24 , quantum diffusion 4,5,23,32 , transient enhanced diffusion and intermixing 17,31 , transient cluster burrowing 22 , ultrafast adatom island nucleation 24 , coherent ballistic displacement of atoms 16 , the cooperative enhancement of surface roughening 66 , the facilitated intermixing near step edges 67 or the superdiffusive mixing in plastically deformed solids 69 .…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of the mechanism could help to explain and classify various athermal atomic transport processes known in the literature such as superdiffusion on solid surfaces 5,14,15,24 , quantum diffusion 4,5,23,32 , transient enhanced diffusion and intermixing 17,31 , transient cluster burrowing 22 , ultrafast adatom island nucleation 24 , coherent ballistic displacement of atoms 16 , the cooperative enhancement of surface roughening 66 , the facilitated intermixing near step edges 67 or the superdiffusive mixing in plastically deformed solids 69 .…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34][35][36] Despite the large number of studies, the underlying deformation-induced mixing processes and the critical factors defining the maximum solubility are still under debate. [33,[37][38][39] Several studies indicate a strong link between the heat of mixing and the degree of supersaturation. In systems with low positive heat of mixing, as for example, Cu-Ag, complete solid solutions are easily reached over the whole composition range during ball milling.…”
Section: Introductionmentioning
confidence: 99%
“…This result agrees with a previous study on the dissolution of spherical precipitates using MD computer simulations, which had shown that shear mixing is superdiffusive, and that the strain required to dissolve small spherical precipitates of radius R p scales with 1 / R p , which again is distinct from the 1 / R p 2 scaling for Fickian diffusion. 32 For multilayered structures, for example ARB, the signature of superdiffusive mixing is far more subtle and it could lead to incorrect conclusions being drawn from experimental studies of the mixing process, as we briefly illustrate.…”
Section: B Model Of Shear Mixing: Monte Carlo Simulationsmentioning
confidence: 94%